Intrawound Treatment for Prevention of Surgical Site Infections in Instrumented Spinal Surgery: A Systematic Comparative Effectiveness Review and Meta-Analysis. Issue 2 (April 2019) - Lemans, Justin V. C.; Wijdicks, Sebastiaan P. J.; Boot, Willemijn; Govaert, Geertje A. M.; Houwert, R. Marijn; Öner, F. Cumhur; Kruyt, Moyo C.
Study Design: Systematic review and meta-analysis. Objectives: To determine the efficacy of intrawound treatments in reducing deep surgical site infections (SSIs) in instrumented spinal surgery. Methods: The electronic databases MEDLINE, EMBASE, and Cochrane were systematically searched for intrawound treatments for the prevention of SSIs in clean instrumented spine surgery. Both randomized controlled trials and comparative cohort studies were included. The results of included studies were pooled for meta-analysis. Results: After full text- and reference screening, 20 articles were included. There were 2 randomized controlled trials and 18 observational studies. Sixteen studies investigated the use of intrawound antibiotics, and 4 studies investigated the use of intrawound antiseptics. The relative risk of deep SSI for any treatment was 0.26 (95% confidence interval [CI] 0.16-0.44, P < .0001), a significant reduction compared with controls receiving no treatment. For patients treated with local antibiotics the relative risk was 0.29 (95% CI 0.17-0.51, P < .0001), and patients treated with local antiseptics had a relative risk of 0.14 (95% CI 0.05-0.44, P = .0006). Conclusions: Both the use of antibiotic and antiseptic intrawound prophylactics was associated with a significant 3 to 7 times reduction of deep SSIs in instrumented spine surgery. No adverse events were reported in the included studies.